Weibliche Genitalbeschneidung im Kontext von Migration - Ihring, Isabelle, 1978- (Budrich UniPress Ltd., 2015)
Female circumcision is a phenomenon that causes different reactions from different perspectives. How do Somali women experience the practice in the context of migration? And what view do social workers and migrated Somali men have of female circumcision? Overall, it is clarified that the perspective of affected women and men in social work will have to be given much more future consideration.